The KαL¹, KαL², and KαL³ X-Ray Emission of Aluminium under Electron Impact - Al-Omari, M.A.M.; Borovyi, M.O. (Металлофизика и новейшие технологии, 2018)
The relative intensities, γ=I(KαL¹)/I(Kα₁,₂), η=I(KαL²)/KαL¹ and χ=I(KαL³)/I(KαL¹), of x-ray emission Kα₁,₂, KαL¹, KαL², and KαL³ lines’ groups of aluminium are experimentally studied under the excitation by electron impact in the range of accelerating voltages U= 4.5–100 kV.